Biological and phytochemical studies of five Malaysian Uncaria species / Hashimah Mohd Hashim - Mohd Hashim, Hashimah (2009)
In this study, five species of Uncaria (family Rubiaceae) also known as “Gambir” widely used as traditional medicine in Malaysia were evaluated for their biological activities as well as phytochemical and total phenolic contents. They are U. calophylla, U. acida, U. lucida, U. cordata and U. longiflora var pteropoda. The methanolic extracts of the plants are subjected to various bioassays including antioxidant, radical scavenging (by 1,1-diphenyl-2-picrylhydrazyl or DPPH) method, antimicrobial (by hole-plate diffusion method) and antihyperglycemic assay (in-vitro inhibition of α-glucosidase enzyme and in-vivo assay). The total phenolic content (TPC) of the plants was evaluated by the Folin-Ciocalteau method. All tested extracts exhibited very strong antioxidant potential (>85% inhibition) in the FTC and TBA assays. In the DPPH assay, U. longiflora (stems and leaves) showed strong radical-scavenging properties with IC50 values of 8-10 µg/ml comparable to vitamin C. In the antimicrobial assay, most extracts displayed good antimicrobial activity against Gram-positive bacteria. U. longiflora was found to inhibit Candida albicans with MIC value of <1.0 µg/ml for both leaves and stems comparable to cyclohexamide. In the in-vitro and in-vivo assays, U. longiflora (stems), U. acida (leaves) and U. cordata (stems) showed very good antihyperglycemic potential. On the basis of chemical and biological screening, U. longiflora (stems) was selected for phytochemical investigation. Repeated chromatographic techniques on the bioactive fraction resulted in the isolation of two major compounds ULs1 and ULs2 identified as pentacyclic alkaloids isomitraphylline and isopteropodine based on 1H and 13C NMR spectroscopic data. ULs1 exhibited stronger antioxidant and α-glucosidase activities than ULs2 which could relate to better immuno-modulatory properties of isomitraphylline. In the αglucosidase inhibitory assay, these two compounds also showed dose-dependent activities indicating their potential as antihyperglycemic agents for type II diabetes.